Divergent functions of NLRP7 in embryogenesis, inflammation and oncogenesis - Garipcan, Aybüke. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
NLRP7 is a novel protein about which we have limited information. To date, mutations in NLRP7 gene have been associated with recurrent Complete Hydatidiform Mole (RCHM) and NLRP7 is accepted to be the first causative gene for RHM. CHM is a gestational disease characterized by hyper trophoblast proliferation with no embryo formation. Furthermore, NLRP7 expression was found to be elevated in testicular seminoma, endometrium cancer and embryonal carcinoma. Yet, the possible mechanisms of action of NLRP7 in these biological conditions or pathways have not been enlightened. In this thesis, we generated patient derived induced Pluripotent Stem Cells (iPSC) to address the role of NLRP7 in HM. We revealed that inadequate NLRP7 levels expedited the di↵erentiation of iPSCs towards the trophoblasts through BMP4. Recovery of NLRP7 expression or BMP pathway inhibition decelerated excessive di↵erentiation of patient iPSCs to trophoblasts. Also, as NLRP7 is an NOD Like Receptor Family member, it is expected to play a role in innate immunity. We have found that infection of human monocytic cells with Pseudomonas aeruginosa activated the NLRP7 inflammasome followed by increased IL-1! secretion. Clearly, stable overexpression of NLRP7 is correlated with increased secretion of pro-inflammatory cytokines such as; TNF-alpha, IL-6, i-309. In addition, to elucidate the possible proto-oncogenic role of NLRP7 in tumorogenesis, we performed xenograft experiments in vivo. We found that stable expression of NLRP7 in the endometrial cancer cell line (Hec1a) resulted in increased tumor growth. Furthermore, potential interaction partners of NLRP7 were identified after co-immunoprecipitation followed by mass spectrometry. Our results shed further light to the overlapping and diverging molecular pathways regulated by NLRP7 in embryogenesis, inflammation and oncogenesis.
Keywords: Immune system.; Embryology.; Inflammation.; Carcinogenesis.